Estudio de prefactibilidad para la instalación de una planta productora de crema de pecanas (Carya illinoinensis) con miel de abeja - Sanchez Avalos, Antonella Rocio Maria (2020)
The present research project evaluates the pre-feasibility of the installation of a pecan cream with honey production plant. This product contains many beneficial properties for health, which makes it attractive to the market. Pecan cream will be segmented to the public that belongs to socioeconomic level A, B and C1 who are 18 years old and older and who reside in zone 7 and 8 of Metropolitan Lima. With the results of the 392 surveys, it was found that 85,80% would be willing to buy the product and 74,50% of purchase’s intention. For the percentage of market share, the result is 63,92%. With the previous information, the demand for the first year of the project was determined to be 28 336,93 kg, equivalent to 141 685 bottles. In relation of the macro location, there are 3 alternatives that were evaluated: Lima, Ica and Ancash, of which Lima was chosen through the factor ranking method. For the micro location, the industrial park of the south of Lima was chosen, in which the districts of Villa El Salvador, Lurin and Chilca are located, the same method was used, from which Chilca was obtained as the headquarter for the plant. On the other hand, the process of producing consists of the following activities: peeling, washing, roasting, crushing, heating, packaging and labeling, performing a quality control at each stage of the process. Finally, it is required a total investment of S/.1 080 953,49, which will be financed by 40% and the rest will be through equity. An economic VAN of S/.525 634,66 and a TIR of 33,50% evaluated in 5 years with a COK of 18%, B/C 1,49 and PR 3 years and 2 months. In the case of the financial analysis a VAN of S/.616 721,33 and a TIR of 44,41% evaluated in 5 years with a COK of 18%, B/C 1,95 and PR 2 years and 10 months. This information determines that the research project is feasible.